Novel gene fusion of PRCC–MITF defines a new member of MiT family translocation renal cell carcinoma: clinicopathological analysis and detection of the gene fusion by RNA sequencing and FISH. Issue 5 (10th January 2018) - Xia, Qiu‐Yuan; Wang, Xiao‐Tong; Ye, Sheng‐Bing; Wang, Xuan; Li, Rui; Shi, Shan‐Shan; Fang, Ru; Zhang, Ru‐Song; Ma, Heng‐Hui; Lu, Zhen‐Feng; Shen, Qin; Bao, Wei; et al.
Abstract : Aims: MITF, TFE3, TFEB and TFEC belong to the same microphthalmia‐associated transcription factor family (MiT). Two transcription factors in this family have been identified in two unusual types of renal cell carcinoma (RCC): Xp11 translocation RCC harbouring TFE3 gene fusions and t(6;11) RCC harbouring a MALAT1–TFEB gene fusion. The 2016 World Health Organisation classification of renal neoplasia grouped these two neoplasms together under the category of MiT family translocation RCC. RCCs associated with the other two MiT family members, MITF and TFEC, have rarely been reported. Herein, we identify a case of MITF translocation RCC with the novel PRCC–MITF gene fusion by RNA sequencing. Methods and results: Histological examination of the present tumour showed typical features of MiT family translocation RCCs, overlapping with Xp11 translocation RCC and t(6;11) RCC. However, this tumour showed negative results in TFE3 and TFEB immunochemistry and split fluorescence in‐situ hybridisation (FISH) assays. The other MiT family members, MITF and TFEC, were tested further immunochemically and also showed negative results. RNA sequencing and reverse transcription–polymerase chain reaction confirmed the presence of a PRCC–MITF gene fusion: a fusion of PRCC exon 5 to MITF exon 4. We then developed FISH assays covering MITF break‐apart probes and PRCC–MITF fusion probes to detect the MITF gene rearrangement. Conclusions: This study both proves the recurring existence of MITF translocation RCC and expands the genotype spectrum of MiT family translocation RCCs.